Registration of Two Allelic Erect Leaf Mutants of Sorghum. Issue 2 (10th April 2015) - Xin, Zhanguo; Gitz, Dennis; Burow, Gloria; Hayes, Chad; Burke, J. J.
Abstract : Two allelic sorghum [ Sorghum bicolor (L.) Moench] erect leaf ( erl ) mutants were isolated from an Annotated Individually‐pedigreed Mutagenized Sorghum (AIMS) mutant library developed at the Plant Stress and Germplasm Development Unit at Lubbock, TX. The two mutants, erl1‐1 (Reg. No. GS‐739, PI 673426) and erl1‐2 (Reg. No. GS‐740, PI 673427), were isolated from two independently pedigreed M3 families mutagenized with ethyl methanesulfonate in a prominent sorghum inbred line, BTx623, which was used to sequence the sorghum genome. Both mutants were backcrossed three times to the wild‐type (WT) BTx623 and shown to be a stable recessive mutation on a nuclear gene. The F1 plants of a cross between the two mutants displayed the erect leaf phenotype, indicating the mutations that result in the erect leaf phenotype in the two mutants are allelic. Both mutants have upright and slightly short leaves and reduced height. The panicles from both mutants are smaller than WT even after three backcrosses. As a highly penetrant trait mediated by a single gene, these mutants may serve as a novel resource to design canopy architecture for optimizing radiation capture and use efficiency to increase biomass and grain yield.